The Relationship Between Foreign Language Classroom Anxiety, Enjoyment, and Expectancy-Value Motivation and Their Predictive Effects on Chinese High School Students’ Self-Rated Foreign Language Proficiency - Dong, Lianqi; Liu, Meihua; Yang, Fan (Frontiers in Psychology, 2022)
The present study explored the relations among foreign language (FL) classroom anxiety, enjoyment, expectancy-value motivation, and their predictive effects on Chinese high school students’ self-rated FL proficiency. Participants were 280 senior high school Chinese EFL (English as a foreign language) learners who were surveyed on their FLCA (foreign language classroom anxiety), FLE (foreign language enjoyment), and expectancy-value motivation. Results showed that 1) the students generally experienced a medium to a high level of FL classroom emotions with FLE slightly higher than FLCA. They were more value-motivated than expectancy-motivated toward FL learning. Most of them perceived their FL proficiency as unsatisfying; 2) the students’ FLE was significantly positively correlated with all dimensions of expectancy-value motivation, while their FLCA demonstrated a complex correlational pattern with components of expectancy-value motivation. As the students’ FLCA level increased, their expectancy beliefs, intrinsic value, attainment value, and utility value decreased, but their cost value increased. By contrast, as their FLE level increased, their expectancy beliefs, intrinsic value, attainment value, utility value all increased, while their cost value first increased and then slightly decreased; and 3) expectancy beliefs, intrinsic value, private enjoyment in FL learning and anxiety arising from fear of negative evaluation jointly significantly predicted the students’ self-rated FL proficiency. Implications for future research and teaching were also discussed.